பழந்தமிழ் இலக்கியத்தில் பரத்தையர் மற்றும் குடும்ப அறம்: Courtesans (Parathaiyar) and Family Virtue in Ancient Tamil Literature - செல்வாம்பாள் வீ (KALANJIYAM - International Journal of Tamil Studies, 2026)
The word Aram (virtue/morality) holds a broad meaning. All human actions can be encompassed within this term. Literature categorizes these actions into good and evil. Tamil literature subtly yet clearly demonstrates how virtue has been practiced in both the internal (Aham) and external (Puram) spheres of Tamil life.Family virtue serves as the foundational ethical structure of Tamil society. The relationship between husband and wife, attachment, chastity (Karpu), responsibility, and discipline constitute the core elements of family life. Highlighting this, the Thirukkural emphasizes the elevated status of family virtue and explains that it is essential for the stability and guidance of society.In the love literature (Aha Ilakkiyam) of the Sangam era, courtesans (Parathaiyar) appear as unavoidable figures. Elements concerning separation due to courtesans can be found in the love poems of Sangam literature, occurring predominantly in Marutham Thinai (poems of the agricultural landscape). As far as the Sangam period is concerned, courtesanry (Parathaimai) was considered an accepted practice or code of conduct. Literature records that a courtesan was not merely a source of pleasure for the hero (Thalaivan) but also functioned as another wife. Accordingly, Sangam literature depicts the hero visiting courtesans, the heroine (Thalaivi) engaging in amorous feid/sulking (Oodal), the hero appeasing the heroine's sulking by using their child as a mediator, and the courtesan holding and fondling the hero's child.Although courtesans were generally considered to be involved in relationships incompatible with a virtuous life, they are still featured with respect in certain places within Sangam literature. Therefore, this study attempts to examine the status of courtesans in family life and their associated virtues..